Bobby Jackson's Sore Knee - Marshall Anderson (Association of American Medical Colleges, 2007)
Abstract This problem-based learning (PBL) case is suitable for either first-or second-year medical students. The case follows a patient with sickle cell anemia over a period of years through numerous sickling crises. Upon completion of this case, students will be able to understand the principles of hemoglobin function; protein structure-function; sickle cell anemia; the differentiation between various types of anemia, mutations, and their effect on the protein products; and how treatment modalities for a disease change over time as we gain more knowledge about the disease. This is one of the most popular cases at the Indiana School of Medicine, and has been used in our PBL course since 1990. It was adapted for use as a teaching case at a preconference workshop on PBL at the Ottawa Conference in Cape Town, South Africa in 2000.